Reflexões sobre a composição de músicas de compositores (as) brasileiros (as) nos cursos de oboé das instituições de ensino superior do Brasil de 2016 a 2021 - Nascimento, Junielson de Paula (2022)
The present work is the result of our restlessness about the insertion of music by Brazilian composers in Brazilian higher education institutions. The advent of oboe teaching in Brazil dates back to the Joanino period, when several art institutions were created with the arrival of the court, among them the Imperial Conservatory of Music. Due to Portugal's influence, the teaching model adopted was the European conservatory, which includes in its repertoire the European baroque, classical and romantic styles, essential in the oboist's education. This model allows for the technical and musical development of the students, but does not stimulate dialogue with other pedagogical possibilities. Thus, the objective of the present research is to reflect on the pedagogical model adopted in Brazil and to contribute to the expansion of the musical panorama for the oboe, especially regarding the Brazilian repertoire. The research was conducted in four stages. In the first stage, we carried out a bibliographic review to understand the process of construction of the repertoire of Brazilian composers for oboe, to understand the development of oboe teaching in Brazil, as well as to select methodological procedures that would allow us to obtain the background for this research. The second step was to apply semi structured questionnaires to the teachers and students. The third stage consisted of a documental research of the recital programs of the oboe class at UFPB. Finally, the fourth step was to analyze the questionnaires based on the theoretical framework and on the cross referencing of the data obtained in the questionnaires of the teachers, students and the documentary research, resulting in an overview of theinsertion of the repertoire of Brazilian composers in Brazilian higher education institutions. The discussion about the oboe teaching model is still very incipient, for this reason it is necessary to establish a reflective process that conceives new pedagogical possibilities, which contemplate the most diverse matrixes that compose the mosaic of musical making and consequently expand the repertoire in Brazilian higher education institutions providing the insertion of Brazilian composers' music.